Peran Badan Usaha Milik Kampung (Bumkam) Dalam Mendukung Pembangunan Desa Di Kecamatan Tualang Kabupaten Siak - Milla, Milla Achliza Putri; Taryono, Taryono; Desweni, Selly Prima (Journal of Social and Policy Issues, 2023)
The establishment of village-owned enterprises (BUMKam) was initiated as a driving force for the village economy and a desire for the welfare of the community. This is because the community's need for a high economy. This study aims to determine and analyze the role of BUMKam in increasing village original income (PAK). The author took 8 BUMKam in Tualang District. The data in this study were taken from secondary data and primary data obtained from the annual BUMKam financial reports and conducted in-depth interviews with 24 informants, namely village chiefs and BUMKam managers. This study uses a quantitative descriptive analysis method by analyzing maps and describing data. Based on the results of the study, it was illustrated that in increasing the village's original income it was influential but not significant and there were still obstacles that occurred. For this reason, the authors suggest that BUMKam be able to further increase revenue in the following year by continuing to develop its business units and it is hoped that it can increase community empowerment in the future.